Detrimental Effects of an Electronic Health Records System on Musculoskeletal Symptoms among Health Professionals. (September 2014) - Hedge, Alan; James, Tamara
A survey of 204 health professionals (physicians, physicians' assistants and nurse practitioners) in private diagnostic clinics of a major healthcare system was conducted after the introduction of an electronic health records (EHR) system. Results showed considerable daily use of computers in various configurations and some 90% of respondents said the EHR had substantially increased their daily computer use. Less than half of the health professionals found the EHR easy to use. Almost half of the physicians said that use of the EHR reduced their face-to-face interactions with patients. Around two-thirds of respondents reported increased frequency of neck, shoulder and back discomfort and some 50% reported an increased frequency of right wrist discomfort since introduction of the EHR. Results demonstrate the importance of incorporating ergonomic workstation designs and ergonomics education when an EHR is being implemented.